Chemical and enzymatic fragmentation of tetanus toxin and immunological studies on anti-tetanus toxin and toxoid sera. - Michaelides, Alecos. (University of Ottawa (Canada), 1996)
This thesis describes the immunization protocols for the production of antibodies against tetanus toxin and toxoid in guinea pigs and mice. Antibodies were successfully raised against the toxin without mortalities in either species. The murine sera obtained, were isotyped by ELISA and the toxin was proven to be a superior antigen in eliciting production of IgG$\rm\sb{2a}$ and IgG$\sb3$. The two isotypes which have demonstrated antitumor activity. The anti-toxoid sera exhibited a lower reactivity towards the toxin and toxoid when compared with anti-toxin sera. The reactivity of recombinant tetanus toxin fragment C was studied and the results indicated that in the murine serum, 72% of anti-toxin or anti-toxoid antibodies were directed against epitopes on fragment C. The study of the guinea pig sera suggested that similar to mouse serum, it can develop in response to toxin as an antigen, antibodies against toxin which are mostly directed against the fragment C portion. On the other hand. guinea pigs seem to respond to the toxoid as an antigen by producing antibodies to more than fragment C. (Abstract shortened by UMI.)
Keywords: Chemistry, Biochemistry.